2010
DOI: 10.1007/s11605-010-1331-7
|View full text |Cite
|
Sign up to set email alerts
|

Transoral Incisionless Fundoplication 2.0 Procedure Using EsophyX™ for Gastroesophageal Reflux Disease

Abstract: At short-term follow-up, the TIF procedure is associated with an excessive early symptomatic failure rate, and a high surgical re-intervention rate. This procedure should not be performed outside of a clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 21 publications
2
37
1
Order By: Relevance
“…We did not experience any gastric or esophageal perforations or bleeding as previously reported in prior studies where the rates of significant bleeding requiring transfusion or gastroesophageal perforations have ranged from 0 to 8% and from 0 to 5%, respectively [5,7,8,10,11,20,21]. One patient did have a minor proximal mucosal tear, from device insertion, which required no additional therapy.…”
Section: Discussionsupporting
confidence: 51%
“…We did not experience any gastric or esophageal perforations or bleeding as previously reported in prior studies where the rates of significant bleeding requiring transfusion or gastroesophageal perforations have ranged from 0 to 8% and from 0 to 5%, respectively [5,7,8,10,11,20,21]. One patient did have a minor proximal mucosal tear, from device insertion, which required no additional therapy.…”
Section: Discussionsupporting
confidence: 51%
“…Only one, fairly recent study concluded that, at short-term follow-up, the TIF procedure was associated with an excessive early symptomatic failure rate and a high surgical re-intervention rate [32]. The present study assessed the results of the TIF 2.0 procedure at 6 months, 1 and 2 years in a series of patients with documented GERD; it also attempted to identify anatomical, functional, and procedure-related factors influencing successful outcome.…”
Section: Discussionmentioning
confidence: 96%
“…One center reported disappointing results with complications including an esophageal perforation, hemorrhage requiring transfusion, and permanent tongue numbness. Device failure using TIF 2.0 occurred in 3/19 cases (15.8%) with 10/19 patients converted to laparoscopic fundoplication [14]. The efficacy of the procedure could possibly correlate with the experience of the surgeon, but this stresses the potential complications of the TIF procedure.…”
Section: Discussionmentioning
confidence: 99%